The Relationship between Self-Adjustment and Anxiety Level of Students at Universitas Aisyiyah Yogyakarta, Indonesia - Ulya, Rafikatul; Katana, Siratia; Jannah, Salsabila Raudhotul (The Indonesian Institute of Science and Technology Research, 2023)
This study aimed to determine whether there is a relationship between self-adjustment and anxiety levels in Yogyakarta students. This research is a quantitative research that uses correlational methods. The sample in the study was 'Aisyiyah Yogyakarta students with vulnerable ages 18-21 years. The model used in this study was 122 respondents with purposive sampling techniques. The data analysis used in this study was product Pearson moment. The results of the hypothesis test show that anxiety has a relationship with self-adjustment with a significance level of 0.000 <0.05, meaning that there is a relationship between anxiety and self-adjustment experienced by 'Aisyiyah Yogyakarta students with the direction of a negative association that can be assumed where the higher the anxiety, the lower the adjustment experienced by 'Aisyiyah students Yogyakarta. There is a significant negative relationship between anxiety and self-adjustment in 'Aisyiyah Yogyakarta students, so the higher the anxiety experienced, the lower the adjustment in 'Aisyiyah Yogyakarta students, and vice versa if the more the anxiety experienced by 'Aisyiyah Yogyakarta students, the higher the adjustment experienced by 'Aisyiyah students ' Yogyakarta.